Referenciação e pronomes relativos em interface no ensino de Língua Portuguesa - Santiago, Vanessa Rodrigues Gomes (2025)
This dissertation focuses on relative pronouns in interface with the referencing process development in texts written by high school students. Based on this approach, the work was guided by the following research questions: a) How do students use relative pronouns in their textual productions? b) To what extent does the approach to the referencing process contribute to the understanding of relatives in referential progression? c) How can studies on the referencing process contribute to the teaching of relative pronouns in textual productions? The purpose of this study is to investigate the use of relative pronouns in textual productions of high school students, with regard to the referencing process and referential progression. In this direction, the specific objectives are outlined as follows: a) to identify, describe, and verify the use of relative pronouns in the written productions of high school students b) To discuss relative pronouns concerning the process of referencing in referential development c) To discuss some implications for teaching relative pronouns in written productions based on the results obtained. The present research is grounded on studies on relative pronouns in normative and usage-based grammars (Bechara, 2016; Cunha; Cintra, 2007; Neves, 2011; 2018; Travaglia, 1996; 2003). In conjunction, it is supported by Textual Linguistics with regard to referencing in texts (Mondada; Dubois, 1995; 2015; Koch, 2005; 2006; 2008; 2013; 2003; 2020; Marcuschi, 2007; Cavalcante e Cavalcante et al, 2014, 2012, 2013; 2022; Cavalcante; Custódio Filho; Britto, 2014). The corpus for this study are made of argumentative essay texts produced by final-year high school students, from which derivations of analyses of the use of relative pronouns in the process of referencing in referential progression are obtained. Thus, the corpus analysis highlights perspectives on grammar teaching that consider real language usage in conjunction with the studies of Textual Linguistics